Implementation of portfolio assessment in teaching English writing - Zuhri Efendi; Bustami Usman; Asnawi Muslem (English Education Journal, 2017)
The objectives of this study were to investigate whether the implementation of portfolio assessment improved students’ writing skills and responses. The method used in this research is pre-experimental with a one-group pre-test and post-test design and descriptive analysis of the students’ responses after the implementation of portfolio assessment for teaching English writing. The population for this research was all students from grade X at SMKN 1, in Banda Aceh and the sample was 30 students chosen by a purposive sampling technique. The data was collected through tests (a pre-test and a post-test) and a questionnaire. The questionnaire was distributed after the post-test to find out the responses of the students after the teaching-learning process using portfolio assessment for writing. The data collected from the tests was analyzed using a t paired sample test through SPSS 16. The results showed that implementation of portfolio assessment improved the’ writing skills and the responses of the students. Therefore, the hypotheses of this study were accepted. There was a significant improvement in the students’ writing skills and their responses after teaching by using portfolio assessment. It was concluded that the use of portfolio assessment can increase students’ writing skills and their responses.